(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) performance, green innovation, and firm size on firm value. The empirical study was conducted on non-financial companies in Indonesia from 2020 to 2023 that were listed in the PROPER category. A total of 24 companies met the data completeness criteria. The data were analyzed using multiple regression analysis with the assistance of SPSS software. The results show that, simultaneously, the independent variables have a significant effect on firm value. However, partially, the ESG score and firm size have no significant effect on firm value, while green innovation has a negative and significant effect on firm value. The findings suggest that green innovation has not yet succeeded in increasing firm value, possibly because its positive impact tends to materialize over the long term.